2019
DOI: 10.3390/su11226413
|View full text |Cite
|
Sign up to set email alerts
|

Decision-Making and Performance Analysis of Closed-Loop Supply Chain under Different Recycling Modes and Channel Power Structures

Abstract: The recycling and remanufacturing of e-waste is linked to a worldwide emphasis on the establishment and implementation of Extended Producer Responsibility system (ERP), which has become an important problem in the process of cycling economy. Meanwhile, with the development and expansion of large-scale retail enterprises, the power structure of supply chain channels is showing a tendency towards diversity as well. However, few studies on closed-loop supply chains (CLSC) have considered both recycling modes and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 62 publications
1
18
0
Order By: Relevance
“…The similar result can be found in Gong et al [19], where authors emphasized that it is always advantageous for manufacturers and retailers to participate in recycling at the same time in terms of the sustainability and profitability of CLSCs. Hence, the manufacturer and retailer are expected to benefit even more from a cooperative effort when implementing green innovation strategies.…”
supporting
confidence: 85%
See 3 more Smart Citations
“…The similar result can be found in Gong et al [19], where authors emphasized that it is always advantageous for manufacturers and retailers to participate in recycling at the same time in terms of the sustainability and profitability of CLSCs. Hence, the manufacturer and retailer are expected to benefit even more from a cooperative effort when implementing green innovation strategies.…”
supporting
confidence: 85%
“…Cheng et al [51] discussed the relationship between environmental responsibility transfer and market power structure and showed that regardless of who decides upon environmental responsibility transfer, a manufacturer as a game leader may make the environmental and economic performance worse. Gong et al [19] analyzed the effects of three types of recycling modes in manufacturer-led and retailer-led CLSCs. Their results confirmed that regardless of who has leadership, a hybrid recycling mode outperforms in terms of the overall supply chain profit and recycling performance.…”
Section: Power Structuresmentioning
confidence: 99%
See 2 more Smart Citations
“…In the field of closed-loop supply chain, lots of scholars has adopted game theory to investigate the optimal pricing decisions [18][19][20][21]; cooperation and coordination of member enterprises [22][23][24][25][26][27]; reverse channel design [28][29][30][31][32], etc. These studies focus on the downstream and reverse logistics of supply chain, and provide positive guidance for the decision optimization of 'manufacturer-retailer', 'manufacturer-remanufacturer', and 'manufacturer-retailer-recycler/remanufacturer' under product remanufacturing strategy.…”
Section: The Game Theory Models In Closed-loop Supply Chainmentioning
confidence: 99%